1989
DOI: 10.1007/bf00155090
|View full text |Cite
|
Sign up to set email alerts
|

Visual function in multiple sclerosis

Abstract: 126 patients with multiple sclerosis and normal visual acuity were submitted to a battery of tests of visual function. The investigation included visual evoked potential, contrast sensitivity by three methods, and a segment of the Farnsworth-Munsell 100 Hue test. 22 of the patients gave a history of unilateral acute optic neuritis and in these the abnormalities were greater in degree. Contrast sensitivity emerged as the most useful test and was abnormal in 92.2% of eyes. Visual evoked potential was delayed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
5

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
1
18
1
5
Order By: Relevance
“…Although previous studies have shown subclinical involvement of the visual pathways in MS [1,3,15,16] they have not been longitudinal as in our study. However, the Optic Neuritis Treatment Trial drew attention to the long-term effect of the subclinical activity in a MS subgroup [34].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Although previous studies have shown subclinical involvement of the visual pathways in MS [1,3,15,16] they have not been longitudinal as in our study. However, the Optic Neuritis Treatment Trial drew attention to the long-term effect of the subclinical activity in a MS subgroup [34].…”
Section: Discussioncontrasting
confidence: 64%
“…This subclinical involvement has thereafter been found frequently in MS patients with VEP and psychophysical determinations of contrast sensitivity [1,3,15,16]. High-pass resolution perimetry was used in this study.…”
Section: Discussionmentioning
confidence: 98%
“…[3][4][5][6][7][8][9] Patients may remain impaired for edge detection (e.g., walking stairs), night vision, stereopsis, and motion detection. Further, when factors known to precipitate Uhthoff phenomena are present, VA can be compromised.…”
mentioning
confidence: 99%
“…One of the characteristic signs of multiple sclerosis (MS), both clinically and sub-clinically, is demyelinizating optic neuropathy [1,2,3,4,5]. The diagnosis of MS is evident in cases of acute retrobulbar optic neuritis (ON); however, ON might also occur silently at any time during the course of MS.…”
Section: Introductionmentioning
confidence: 99%